Pengaruh Modifikasi Latihan Permainan Bola Futsal Terhadap Kemampuan Dribbling Pada Tim Futsal UNIMUDA Sorong - Laurens Ijie, Dominggus; Istiyono; Sugiono (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This research aims to determine the effect of modified futsal ball training on the dribbling abilities of the UNIMUDA Sorong futsal team. This research method uses an experimental method with a pre-test and post-test design. The research sample was 20 people. The results showed a significant increase in players' dribbling abilities after following the modified training program. The average initial dribbling time was 13.1 seconds, while the average final dribbling time was 11.4 seconds, with an average decrease in dribbling time of 1.7 seconds. The average percentage increase in dribbling ability was 13%, which shows the effectiveness of the implemented training program.